PROBLEMS OF EVALUATION OF INVESTMENT PROJECTS - Uralova Dilbar Anorboevna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
This article presents ideas and opinions about the problems of evaluating investment projects and methods of evaluating the economic efficiency of investment projects.